Keadilan dan Dukungan Organisasi: Pengaruh terhadap Komitment dan Turnover Intention dengan Dimediasi Keterikatan Karyawan - Verdian, Verdian; Hosen, Chandra (Journal of Business & Applied Management, 2024)
This study aimed to examine the impact of Perceived Distributive Justice, Perceived Procedural Justice, and Perceived Organizational Support on Organizational Commitment and Employees' Intentions to Leave the Company, with Employee Engagement as a mediating factor at PT Tekun Jaya Utama. Additionally, it offers recommendations for PT Tekun Jaya Utama to enhance organizational commitment and mitigate employees' intentions to leave. Employing a quantitative approach, data were collected from 51 respondents through questionnaire distribution among PT Tekun Jaya Utama employees using probability sampling with a simple random sampling technique. Data analysis was conducted using Smart-PLS 3.0 software. The findings shows that the significant effects of justice and organizational support on organizational commitment and employees' intentions to leave. However, the overall mediating effect of employee engagement was found to be insignificant in this study. These results underscore the importance of justice and organizational support in shaping organizational commitment and turnover intentions among employees.